Pengaruh Kualitas Layanan Terhadap Kepuasan Pelanggan: Studi Regresi Pelanggan Bengkel Yamaha Tabrani Jaya Motor Kota Bekasi - Triwibowo, Krisna (Prisani Cendekia Institute, 2025)
This study aims to determine the influence of the SERVQUAL method on customer satisfaction. The purpose of this research is to examine the effect of Tangibles, Reliability, Responsiveness, Assurance, and Empathy on customer satisfaction at Yamaha Tabrani Jaya Motor, Bekasi City. This research applies both descriptive and causal approaches, with each variable measured using a nine-point Differential scale. The study utilizes both primary and secondary data, collected through questionnaires. The sample was obtained using purposive sampling, resulting in 166 respondents. This research uses multiple linear regression statistical methods with SPSS to test the hypotheses. The results show that Tangibles, Reliability, Responsiveness, Assurance, and Empathy all have an influence on Customer Satisfaction at Yamaha Tabrani Jaya Motor, Bekasi City.